Mathematical model of volume kinetics and renal function after burn injury and resuscitation. Issue 2 (March 2021) - Arabidarrehdor, Ghazal; Tivay, Ali; Bighamian, Ramin; Meador, Chris; Kramer, George C.; Hahn, Jin-Oh; Salinas, Jose
Highlights: A mathematical model of blood volume kinetics and renal function in burns. Capability to accurately predict blood volume and urinary output in burns. Basis for in-depth understanding of burn-induced volume kinetic and renal responses. Basis for development and non-clinical testing of burn resuscitation protocols. Abstract: This paper presents a mathematical model of blood volume kinetics and renal function in response to burn injury and resuscitation, which is applicable to the development and non-clinical testing of burn resuscitation protocols and algorithms. Prior mathematical models of burn injury and resuscitation are not ideally suited to such applications due to their limited credibility in predicting blood volume and urinary output observed in wide-ranging burn patients as well as in incorporating contemporary knowledge of burn pathophysiology. Our mathematical model consists of an established multi-compartmental model of blood volume kinetics, a hybrid mechanistic-phenomenological model of renal function, and novel lumped-parameter models of burn-induced perturbations in volume kinetics and renal function equipped with contemporary knowledge on burn-related physiology and pathophysiology. Using the dataset collected from 16 sheep, we showed that our mathematical model can be characterized with physiologically plausible parameter values to accurately predict blood volume kinetic and renal function responses to burn injury and resuscitation on an individual basis against a wide range of pathophysiological variability. Pending validation in humans, our mathematical model may serve as an effective basis for in-depth understanding of complex burn-induced volume kinetic and renal function responses as well as development and non-clinical testing of burn resuscitation protocols and algorithms.